(untitled) (TAMADDUN NURI JURNALI, 2024)
the author of the article focuses on such prerequisites for achieving mutual understanding as perception, empathy, readiness for interaction, and the formation of intercultural competencies. The role of social skills, cognitive component, and empathic abilities in building and developing partnerships and overcoming communication barriers is especially emphasized. The above methods of building trusting partnerships can rightfully be called means of “public diplomacy”, ensuring sincerity and trust in any social interaction and business cooperation.